2012
DOI: 10.1021/ja306062c
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative C–H Coupling of Azoles and Aryl Esters: Unprecedented Nickel Catalysis and Application to the Synthesis of Muscoride A

Abstract: A nickel-catalyzed decarbonylative C−H biaryl coupling of azoles and aryl esters is described. The newly developed catalytic system does not require the use of expensive metal catalysts or silver-or copper-based stoichiometric oxidants. We have successfully applied this new C−H arylation reaction to a convergent formal synthesis of muscoride A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(150 citation statements)
references
References 57 publications
7
134
1
8
Order By: Relevance
“…322 In contrast to the initial mechanistic proposal by Itami, 323,324 calculations at the SMD (dioxane) M06L/6-311+G(2d,p) (SDD+d,f)//B3LYP/6-31G(d) (LANL2DZ) level of theory indicated that in the case of decarbonylative coupling, the C−H activation step takes place before the CO migration (rate-determining step). If the CO migration would take place prior to C−H activation, the formed Figure 23.…”
Section: C−o Bond Activationmentioning
confidence: 83%
See 1 more Smart Citation
“…322 In contrast to the initial mechanistic proposal by Itami, 323,324 calculations at the SMD (dioxane) M06L/6-311+G(2d,p) (SDD+d,f)//B3LYP/6-31G(d) (LANL2DZ) level of theory indicated that in the case of decarbonylative coupling, the C−H activation step takes place before the CO migration (rate-determining step). If the CO migration would take place prior to C−H activation, the formed Figure 23.…”
Section: C−o Bond Activationmentioning
confidence: 83%
“…323 325 The lack of a free coordination site in the case of a bidentate ligand only allows for a threecentered TS. Since the BDE of the O−Acyl bond is lower, this transition state is associated with a low distortion energy.…”
Section: C−o Bond Activationmentioning
confidence: 99%
“…In 2012, Yamaguchi, Itami, and coworkers discovered a nickel-catalyzed decarbonylative C-H coupling between 1,3-azoles and aryl esters and applied these catalytic conditions to the synthesis of muscoride A, a natural product that displays weak antibacterial activity (Scheme 16.28) [59]. Two azole esters, 137 and 138, were coupled under Ni/dcype catalysis to furnish the corresponding product 139 in 39% yield.…”
Section: Texaline Febuxostat and Muscoride A (C-h Arylation Of Oxazmentioning
confidence: 99%
“…The authors reasonably speculated that the decarbonylative C-H arylation protocol involved a Ni0/NiII catalytic cycle (Scheme 38). 61 This novel C-H arylation reaction was successfully applied to a convergent formal synthesis of natural product muscoride A with exceptional antibacterial activity (Scheme 39). …”
Section: Scheme 32mentioning
confidence: 99%